An ACO-Based Trust Inference Algorithm - Leyi Shi; Yao Wang; Xin Liu (IIAI-AAI 2014 : proceedings : 2014 IIAI 3rd International Conference on Advanced Applied Informatics : Kitakyushu, Japan, 31 August - 4 September 2014, 2014)
The trust value between two nodes is important for their interactions in social network . In this paper we propose an ACO-based trust inference algorithm. First, we use the Ant Colony Optimization algorithm to find two trust trains with high trust value between any two nodes, since the most accurate information comes from the node with the highest trust value. We optimized the corresponding parameters of the ACO algorithm to make it adaptive to our problem. Indirect trust value between two nodes is calculated according to direct trust value and trust chains got by ACO. The statistical analysis indicates that our algorithm gains more accuracy of trust value computing compared with a classical trust algorithm.